Analisis Faktor yang Berhubungan dengan Pemanfaatan Jamban Di Kawasan Perkebunan Kopi (Analysis of Factors Associated with the Use of Toilets At Coffee Plantation Region) - Fani Febri Anggoro; Khoiron Khoiron; Prehatin Trirahayu Ningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
The study of Indonesia Sanitation Sector Development Program (ISSDP) in 2006, showed that 47% of people still defecate in open areas. Sidomulyo Village is a coffee plantation area with poor environmental sanitation, which is 91.94% of the villagers still defecate in open areas. This study aims to determine the factors associated with the use of toilets, which are predisposing, enabling, and reinforcing factors. This research is an analytical survey with cross sectional approach. Sampling by multistage random sampling, obtained samples of 70 householders. Data collecting is done by using questionnaires and observation sheets. Data were analyzed using chi square test at α=0.05. The results showed that there were significant relationships between income (pvalue= 0,004), knowledge (p-value=0,000), attitude (p-value=0,000), condition of toilets (pvalue= 0,001), and the availability of clean water (p-value=0,000) with the use of toilets. Meanwhile age (p-value=0.590), occupation (p-value=0.109), education (p-value=0.259), the support of health workers, religious leaders, community leaders, and family (pvalue= 0.400) showed that there were no significant relationships with the use of toilets. Keywords: The use of toilets, predisposing, enabling, and reinforcing factor